THE INFLUENCE OF DYSMENORRHEA EXERCISES TOWARD MENSTRUAL PAIN ON FEMALE STUDENTS AT STIKES DUTA GAMA KLATEN - Aryani .; R. Taufiq Nur Muftiyanto; Witriyani . (STIKES DUTAGAMA KLATEN, 2017)
Background: dysmenorrheal is a pain at the lower abdomen when the menstruation period along with cramps, dizziness and faint. The sore can interfere the activity and it needs medicine. Dysmenorrhea can be treated by using dysmenorrhoe exercises therapy. Objective: the aim of the study is to find out the effect of dysmenorrhea exercises towards the menstrual pain on female students at STIKES Duta Gama Klaten. Research Method: The research type of this study was pre-experiment design research by using one group pre test post test. The sample was taken by purposive sampling technique which consist of 30 respondents.The instrument used in this study is the Numeric rating scale questionnaire. The data were analyzed by paired t-test. Result: The statistical test results obtained p-value 0,000 (p <0.005). Before the treatment there were 20 respondents with moderate pain level and 10 respondents mild pain level. Then after the treatment there were 29 respondents with mild pain level and 1 respondent without any pain. There is influence of dysmenorrhea exercises toward the menstrual pain on female students at STIKES Duta Gama Klaten. Conclusion: Dysmenorrhea exercises have influence on reducing pain when menstruation period on the female students at STIKES Duta Gama Klaten.